uji UJI AKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP MENCIT GALUR BALB/C YANG DIINDUKSI BAKTERI Salmonella sp. - Rahmi Muthia; Yaumi Musfirah; Septiyani Candrakirana (BORNEO JOURNAL OF PHARMASCIENTECH, 2019)
Morinda citrifolia are known to contain tannin active substances asantidiarrheal and anthraquinone as antibacterial. This study aims to determine theoptimal activity and dose of ethanolic extract of Morinda as antidiarrheal induced bySalmonella Sp. Mus musculus divided into 5 groups consisting of 5 mice; controlgroup (CMC-Na 0.5%), the extract group (doses 150, 300, and 600 mg / kgBW) andDiapet NR group (1.3 mg / kgBW). Each group was induced Salmonella sp 1 mlorally. Thirty minutes after induction, the group was given oral treatment andobserved the onset of diarrhea, duration of diarrhea, frequency of diarrhea, fecalweights and antidiarrheal effects for 5 hours. The results showed the best decrease ofdiarrhea onset was EEDM 600 mg / kgBW (51.8 ± 6.53 min), the shortest diarrheaduration was also showed EEDM 600 mg /kg BW (48.8 ± 33.49 min), and the bestdecrease of diarrhea frequency was EEDM 300 mg /kgBW (7.4 ± 1.67 times). Thebest decrease of faecal weight was EEDM 300 mg /kgBW (0.416 ± 0.175 gram) andthe last parameter antidiarrheal effect was also showed EEDM 300 mg / kgBB(43.10%). The conclusions of this study was EEDM has antidiarrheal activity inducedby Salmonella sp bacteria when compared with control and Diapet NR, and EEDM300 mg / kgBW is the optimal dose that given antidiarrheal effects